Enhanced ion tolerance of electrokinetic locomotion in polyelectrolyte-coated microswimmer - Xiaojun Zhan (Nature Portfolio, 2019)
Electrophoretic microswimmers aren’t well suited to function in vivo because electric-field screening reduces their speed in higher ionic-strength solutions. Here the authors propose a microswimmer that exploits high surface conductance to improve this ion tolerance to enable operation in a high salt environment.